Effect of montmorillonite on the crystallization and thermal degradation of poly(propylene-coethylene- co-1-butene) nanocomposites - Riechert, Verónica Mariel (2016)
Polymeric nanocomposites based on poly(propylene-co-ethylene-co-1-butene) (PEBC) were elaborated by melt mixing using an organophilic montmorillonite (o-MMT) and maleated PEBC (PEBCg) as compatibilizer. The effect of clay concentration, PEBCg:o-MMT ratio, and grafting degree of the compatibilizer were studied. X-ray diffraction and scanning electron microscopy show formation of partially intercalated structures in all compatibilized composites with well-distributed small tactoids. According to the differential scanning calorimetry results, the anhydride groups of the compatibilizer have a marginal nucleating effect, while the o-MMT causes a slight decrease in the crystallization temperature of the polymer. PEBC presents the largest activation energy of crystallization (Eα), while the composites show lower Eα than their matrices. It is also observed that the rate of degradation of PEBC is not affected by the presence of PEBCg. The nanoclay, on the other hand, retards the decomposition process of the polymeric matrix in about 40°C and augments its rate of degradation approximately four times.